2015
DOI: 10.3389/fnins.2015.00367
|View full text |Cite
|
Sign up to set email alerts
|

Injury in aged animals robustly activates quiescent olfactory neural stem cells

Abstract: While the capacity of the olfactory epithelium (OE) to generate sensory neurons continues into middle age in mice, it is presumed that this regenerative potential is present throughout all developmental stages. However, little experimental evidence exists to support the idea that this regenerative capacity remains in late adulthood, and questions about the functionality of neurons born at these late stages remain unanswered. Here, we extend our previous work in the VNO to investigate basal rates of proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…Indeed, in a study directly comparing the survival of birth-dated OSNs in mice aged 10 days to 16 months, Kondo et al (2010) found similar reductions in the number of 14-day-old vs. 5-day-old OSNs across mouse age groups. However, both Kondo et al (2010) and another study (Brann et al 2015) reported far greater elimination of OMP-expressing OSNs between 14 and 30 days of neuronal age in mice injected with BrdU at 1-month-old vs. 2-3-months-old. These studies therefore indicate that P28-born OMP-expressing OSNs are less likely to survive long-term than those generated in older mice.…”
Section: Low Survival Rate Of P28-born Osnsmentioning
confidence: 90%
“…Indeed, in a study directly comparing the survival of birth-dated OSNs in mice aged 10 days to 16 months, Kondo et al (2010) found similar reductions in the number of 14-day-old vs. 5-day-old OSNs across mouse age groups. However, both Kondo et al (2010) and another study (Brann et al 2015) reported far greater elimination of OMP-expressing OSNs between 14 and 30 days of neuronal age in mice injected with BrdU at 1-month-old vs. 2-3-months-old. These studies therefore indicate that P28-born OMP-expressing OSNs are less likely to survive long-term than those generated in older mice.…”
Section: Low Survival Rate Of P28-born Osnsmentioning
confidence: 90%
“…On the other hand, mechanical procedures, such as the extraction of the olfactory bulbs (bulbectomy) and the transection of the olfactory nerves (axotomy), induce only ORNs degeneration by depriving their synaptic target. Despite the massive ORN lost, mechanical procedures provoke a mild OE injury in the sense they do not disrupt the general tissue organization (Graziadei et al, 1979; Holcomb et al, ; Takami et al, ; Borders et al, ; Bakos and Costanzo, ; Brann et al, ). Therefore, depending on the experimental approach, it is possible to study neural differentiation, including both neuronal and glial lineages; or specifically analyze neuronal regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…GFP‐labeled cells are present, not only within the main olfactory epithelium, but also in the septal organ or organ of Masera (Figure b), and to a lesser extent in the vomeronasal organ (Figure c). In the vomeronasal organ, GFP‐labeled cells are restricted to the margins of the sensory epithelium, that is, in the areas of cell proliferation and addition in young adults (Brann, Ellis, Ku, Spinazzi, & Firestein, ; Brann & Firestein, ; De La Rosa‐Prieto et al, ; Giacobini, Benedetto, Tirindelli, & Fasolo, ).…”
Section: Resultsmentioning
confidence: 99%
“…In the vomeronasal organ, GFP-labeled cells are restricted to the margins of the sensory epithelium, i.e. in the areas of cell proliferation and addition in young adults (Giacobini et al, 2000; De La Rosa-Prieto et al, 2009; Brann and Firestein, 2010; Brann et al, 2015).…”
Section: Resultsmentioning
confidence: 99%